Síndrome de fragilidade em idosos longevos : análise da composição corporal por ultrassom - Ribeiro, André (2018)
Introduction: Fragility is a common clinical syndrome in the elderly, which causes great risks to health, disabilities, hospitalizations and consequently a high risk of mortality. The available knowledge about the multiple aspects of fragility in the elderly suggests that it is a predictor of changes in body composition, with a decline in lean mass, and in this way, a relevance in the study of the subject in long-lived patients is observed. In this aspect, the present study proposes the use of Ultrasound (US) because it is a portable method, with ease of handling and not be influenced by skinfolds, which minimizes possible inter and intra-rater variations, therefore, with greater reliability in relation to the results presented. Objectives: To identify the characteristics of the body composition through the US in the groups of non-frailty and frailty oldest-old. Methods: The greatest possible number of oldest-old were traced through the Geriatrics General Ambulatory of Hospital São Lucas / PUCRS. Personal and social data were collected through a questionnaire. Fragility data were obtained through five phenotypes. Body composition data were obtained through the portable US. For the analysis of the data, the sample was separated into two groups, according to the classification of fragility: frailty and non-frailty. Percentage differences between the categorical variables were calculated through the creation of cross tables between the variables. Numerical variables were presented through means, standard deviations and variances. Results: 52 elderly people with a mean age of 90.10 ± 4.49 years were evaluated. 63.5% were classified as non-frailty and 36.5% frailty. The majority of the sample is composed of women (73.1%). White race totals 86.5% and 80.5% are widowers. 31.6% of the frailty oldest-old live alone. The average amenities were higher for the frailty (3.21 ± 1.14) compared to non-frailty (2.15 ± 1.67). In the analysis of schooling, those who reported having elementary education (≤ 8th grade) had a higher odds ratio [RP1,22 (CI95% 1.00-1.49)] to develop fragility compared to the reference category (≥ high school) (p = 0.046). Through the classification of the percentage of body fat (%F) by the US, it was observed that the female longevity with scores above 33 %F, presented a higher odds ratio [RP1,81 (IC95% 1,30-2, 52)] to develop fragility compared to the category with the reference %F (<29 %F) (p <0.001). For males, those who obtained scores above 26 %F had a greater chance [RP1,81 (IC95% 1.30-2.52)] of developing fragility compared to the category with the reference %F (<23 %F) (p <0.001).Conclusion: The present study showed persuasive results between fragility syndrome and body composition. Through the analysis of body composition by Ultrasound and according to the points of cuts predicted in the literature, it was possible to identify associations between obesity and increased risk of frailty in longevity. It was concluded that, the higher the body fat levels and the lower the lean mass (sarcopenic obesity), the greater the level of fragility of the longevity above 80 years of age.